2018
DOI: 10.1007/s11033-018-4170-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of QTL-rich region polymorphisms identified by targeted DNA-seq on pig production traits

Abstract: The aim of the present study was to analyse the effect of PLCD4, PECR, FN1 and PNKD mutations on pig productive traits and tested the usefulness of targeted enrichment DNA sequencing method as tool for preselection of genetic markers. The potential genetic markers for pig productive traits were identified by using targeted enrichment DNA sequencing of chromosome 15 region that is QTL-rich. The selected mutations were genotyped by using HRM, Sanger sequencing and PCR-ACRS methods. The association study was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Some reports showed that QTLs for quality, yield, resistance and other important traits of crops were generally distributed in clusters (Kruijt et al, 2004; Teng et al, 2002), such as wheat (Liu et al, 2005), rice (Qu et al, 2005), maize (Abler et al, 1991), sorghum (Lin et al, 1995) and cotton (Shappley et al, 1998). The cluster distribution of QTLs means that QTLs controlling different traits are distributed in a regionalization trend, also known as “QTL hot spots” (Stuczyńska et al, 2018). There are two main reasons for this phenomenon: (i) The QTLs detected present characteristic of the pleiotropism that one gene locus controls multiple traits at the same time; (ii) sometimes, two tightly linked marker‐site can control multiple different traits at the same time; (iii) statistical software could not differentiate between the two similar or adjacent genes located on chromosomes; (iv) single‐functional genes may control a series of traits (Li et al, 2009; Roberto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports showed that QTLs for quality, yield, resistance and other important traits of crops were generally distributed in clusters (Kruijt et al, 2004; Teng et al, 2002), such as wheat (Liu et al, 2005), rice (Qu et al, 2005), maize (Abler et al, 1991), sorghum (Lin et al, 1995) and cotton (Shappley et al, 1998). The cluster distribution of QTLs means that QTLs controlling different traits are distributed in a regionalization trend, also known as “QTL hot spots” (Stuczyńska et al, 2018). There are two main reasons for this phenomenon: (i) The QTLs detected present characteristic of the pleiotropism that one gene locus controls multiple traits at the same time; (ii) sometimes, two tightly linked marker‐site can control multiple different traits at the same time; (iii) statistical software could not differentiate between the two similar or adjacent genes located on chromosomes; (iv) single‐functional genes may control a series of traits (Li et al, 2009; Roberto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…La carga genética de los animales es un factor fundamental que condiciona e incide en las características de rendimiento y en los parámetros de calidad. Se han detectado genes que tienen efecto directo sobre los atributos de la carne (Candek-Potokar et al, 1998;Jeremiah et al, 1999;Wood et al, 1996, Stuczyńska et al, 2018. Muchos de estos genes pueden convertirse en herramientas útiles si son considerados como marcadores moleculares.…”
Section: Introductionunclassified